Apropiaciones y experiencias pedagógicas de filosofía e infancia en Colombia - Suárez Vaca, María Teresa; González Vargas, Bibiana Alexandra; Lara Buitrago, Paola Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 225-247